Enhancing Students Motivation in Japanese Conversation (Online Course): through CM - Pika Yestia Ginanjar (IZUMI, 2020)
This paper focuses on the study and teaching strategy of Japanese conversation. The goal of the paper is to analyze the motivation of the students learning experience through CM as a media source of the study, which can lead students to enhance their level of proficiency. The study used a qualitative method of the case study Japanese conversation lecture. Conversation lectures are usually done by memorizing text or role-play using existing text. The idea of this study is similar to role-play but, through CM students can learn pronunciation, articulation, and intonation from the native (actor) directly. This study represents the first stage of a research project aimed at raising student confidence and enhancing Japanese fluencies. The major finding was that a clear majority of students reported a considerably high motivation according to the use of terms ‘tanoshikatta’ and ‘omoshiroi’ on their feedback. It says that students were interested to do the assessment.